Jeanne Lazarus, Les politiques de l'argent, Paris, Presses Universitaires de France/Humensis, 2022, 336 p. - Dagnes, Joselle (PARTECIPAZIONE E CONFLITTO, 2023)
For Book Reviews Abstract is not Required